Public Satisfaction on Water Utility Services in an Urban Community - Hamsinah Djaing; Sangkala Sangkala; Muhammad Rusdi; Andi Ahmad Yani (Journal of Governance, 2020)
Water utility service is a fundamental service in urban society. Urban citizens expect a high quality of service that made the service provider company should be responsible to provide it. This study aims to examine service quality of water utilizes services which are delivered by the Regional Water Supply Company (RWSC) in the City of Makassar, Indonesia. The method used in this research is the quantitative method through a customer satisfaction survey. The research conducted in the Regional Water Supply Company (RWSC) of Makassar, precisely in four regions. The study employs a stratified sampling method based on regions and the number of the population is 163,549 customers. This study applies 95 percent and margin error is 5 percent which means the number of samples is interviewed not lower than 384 respondents. The data was collected through face to face interviews with questionnaires. The data obtained from the field is processed using a technical analysis of descriptive statistical data. The result shows that the customers of water utility services have moderate satisfaction where technical services are far better than non-technical services.